Empowering Shadow Teachers through Integrated STEAM-Based Learning and Positive Behaviour Support: A Community Service Program for Inclusive Education Teachers - Laily, Nadhirotul; Chamimmah Lailis Indriani, Nur; Hendarwati, Endah; Faizah, Ima; Nisak Aulina, Choirun (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid expansion of inclusive education in Indonesia has increased the demand for competent Shadow Teachers (Guru Pendamping Khusus/GPK) who are able to support children with special needs (ABK) in regular classrooms. However, many teachers at early childhood, elementary, and secondary levels remain underprepared to identify the characteristics of ABK, design individualized learning strategies, manage behaviour and emotional regulation, apply multisensory media, and collaborate with parents. This community service program aimed to strengthen these competencies among 76 teachers from early childhood, elementary, and secondary schools under Majelis Pendidikan Anak Usia Dini, Dasar, dan Menengah (PAUD Dasmen) 'Aisyiyah East Java through a two-day intensive Shadow Teacher training. The program integrated four components: inclusive education foundations, Shadow Teacher professional competencies, STEAM-based inclusive learning, and Positive Behaviour Support, framed within the Pyramid of Learning model. Activities included interactive workshops, simulation, role play, case studies, mini-projects, reflection, and pre-post test evaluation, delivered across three stages: needs assessment, implementation, and evaluation. The program strengthened participants' knowledge of inclusive pedagogy, their skills in designing individualized and multisensory learning, and their confidence in supporting children with special needs, while also fostering an emerging community of practice among Shadow Teachers within the 'Aisyiyah education network. The findings suggest that integrating inclusive education, STEAM, and positive behaviour approaches offers a holistic and replicable model for Shadow Teacher capacity building in faith-based school networks.Pesatnya perluasan pendidikan inklusif di Indonesia meningkatkan kebutuhan akan Guru Pendamping Khusus (GPK) atau Shadow Teacher yang kompeten dalam mendampingi anak berkebutuhan khusus (ABK) di kelas reguler. Namun, sebagian besar guru pada jenjang PAUD, dasar, dan menengah belum memiliki kesiapan memadai untuk mengidentifikasi karakteristik ABK, merancang strategi pembelajaran individual, mengelola perilaku dan regulasi emosi, menggunakan media multisensori, serta berkolaborasi dengan orang tua. Program pengabdian ini bertujuan meningkatkan kompetensi tersebut pada 76 guru PAUD, sekolah dasar, dan menengah di bawah Majelis Pendidikan Anak Usia Dini, Dasar, dan Menengah (PAUD Dasmen) Pimpinan Wilayah 'Aisyiyah Jawa Timur melalui pelatihan intensif Shadow Teacher selama dua hari. Program mengintegrasikan empat komponen: dasar-dasar pendidikan inklusif, kompetensi profesional Shadow Teacher, pembelajaran inklusif berbasis STEAM, dan Positive Behaviour Support, yang dibingkai dalam model Pyramid of Learning. Kegiatan meliputi workshop interaktif, simulasi, role play, studi kasus, mini project, refleksi, serta evaluasi pre-test dan post-test yang dilaksanakan dalam tiga tahap: asesmen kebutuhan, implementasi, dan evaluasi. Program ini memperkuat pengetahuan peserta mengenai pedagogi inklusif, keterampilan menyusun pembelajaran individual dan multisensori, serta kepercayaan diri dalam mendampingi ABK, sekaligus membangun komunitas praktik Shadow Teacher di lingkungan pendidikan 'Aisyiyah. Temuan ini menunjukkan bahwa integrasi pendekatan pendidikan inklusif, STEAM, dan positive behaviour menawarkan model pengembangan kapasitas Shadow Teacher yang holistik dan dapat direplikasi pada jejaring sekolah berbasis keagamaan.